Preface (Preface_V_XXVIII) - Robinson, James M. (BrillOnline Reference Works, 2012)
This volume is the result of a team effort to which seven scholars have contributed. No attempt has been made by the editor to compromise their individual styles or scholarly positions. Clarity, accuracy and formal standardization have constituted the chief editorial tasks. Hence the reader will be aware of the individual stylistic idiosyncrasies of each author